Consumption Growth in a Booming Economy: Taiwan 1976-96 - David J. McKenzie (Yale University, Economic Growth Center, 2001)
Consumption and income have both grown rapidly in Taiwan over the past forty years, with younger birth cohorts experiencing faster growth. The long upward trend in consumption presents a strong challenge to the consumption smoothing predictions of the Permanent Income Hypothesis. We investigate the extent to which consumption theory can account for this trend in an environment where a large majority of households have high savings rates. Household survey data from 1976-96 are used to estimate dynamic pseudo-panel models with inter-cohort heterogeneity. We evaluate the impacts on consumption of migration, mortality, household composition, liquidity constraints, unanticipated aggregate shocks, hyperbolic discounting, habit formation and precautionary saving. Taiwanese consumption growth is found to result from high levels of prudence, with the faster consumption growth of younger cohorts attributed to their greater participation in industries with more earnings risk.Classification-JEL: O12; O16; E21; C23
Keywords: 330; consumption growth; pseudo-panel; prudence; Taiwan; Gesamtwirtschaftlicher Konsum; Einkommen; Einkommenshypothese; Schätzung; Taiwan